Risk of invasive breast cancer in relatives of patients with breast carcinoma in situ: a prospective cohort study - Mukama, Trasias; Fallah, Mahdi; Brenner, Hermann; Xu, Xing; Sundquist, Kristina; Sundquist, Jan; Kharazmi, Elham (BMC medicine, 2020)
Wide implementation of mammography screening has resulted in increased numbers of women diagnosed with breast carcinoma in situ. We aimed to determine the risk of invasive breast cancer in relatives of patients with breast carcinoma in situ in comparison to the risk in relatives of patients with invasive breast cancer.
Gesehen am 29.04.2021